Mobile payment systems : secure network architectures and protocols - Tellez, Jesus; Zeadall, Sherali (Springer Science and Business Media, 2017)
This important text/reference presents the latest research and developments in the field of mobile payment systems (MPS), covering issues of mobile device security, architectures and models for MPS, and transaction security in MPS. Topics and features: introduces the fundamental concepts in MPS, discussing the benefits and disadvantages of such systems, and the entities that underpin them; reviews the mobile devices and operating systems currently available on the market, describing how to identify and avoid security threats to such devices; examines the different models for mobile payments, presenting a classification based on their core features; presents a summary of the most commonly used cryptography schemes for secure communications; outlines the key challenges in MPS, covering security for ubiquitous mobile commerce and usability issues; highlights the opportunities offered by mobile cloud computing and vehicular ad hoc networks in the design and development of MPS.
Keywords: 1. Mobile computing 2. Ubiquitous computing 3. Electronic fund transfer